Educative Value Analysis in The Film “Orang Kaya Baru” - Hana Zhafira Maulita; Marudut Bernadtua Simanjuntak (Jurnal Pendidikan dan Sastra Inggris, 2022)
The main problem in this research is to analyze an educational value in the film "Orang Kaya Baru" which contains the values ​​of life in society. In this film, it depicts a family who has a simple life but does not eliminate the sense of togetherness, they are taught to always be grateful and stay happy in that simplicity, besides that there is a moral message that the author wants to convey about a simple family life and then becoming rich. Objective from study this is known dependency moral messages as well as calculation delivered value in the film This study concludes that the educational values contained in the film "Orang Kaya Baru" are a) social values, namely parents who give advice to their children, please help, until the sense of kinship in the film is lost, b) cultural values, namely when eating, give envelopes. At weddings and eating together with family, c) religious values, namely gratitude, always being patient and not forgetting to always give charity, d) moral values, namely always apologizing, being indifferent, being responsible as a family head, being honest and independent, and creating creative ideas in order to have achievements.